EVALUASI PROGRAM MAGANG MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM MENGGUNAKAN MODEL CIPP - NINING PITRIA Nining Pitria; Ali Nahruddin Tanal; Hasbi Hasbi (Evaluasi : Jurnal Manajemen Pendidikan Islam, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) policy provides opportunities for students to gain direct learning experiences in professional settings through internship activities. The Islamic Education Management Study Program at UIN Palopo has implemented the MBKM internship program as an effort to enhance students’ academic, professional, and practical competencies. This study aims to evaluate the implementation of the MBKM internship program using the CIPP (Context, Input, Process, Product) evaluation model. This research employed a mixed-methods approach, combining qualitative and quantitative data. Qualitative data were collected through interviews, observations, and documentation, while quantitative data were obtained from questionnaires distributed to MBKM internship participants. Qualitative data were analyzed through data reduction, data display, and conclusion drawing, while quantitative data were analyzed using percentage-based descriptive analysis. The results indicate that in the context aspect, the internship program holds strong relevance and urgency for competency development, supported by curriculum alignment and students’ need for workplace experience. In the input aspect, student readiness and supervisor support were generally good, although challenges remained such as unequal prior understanding regarding internship procedures. In the process aspect, the internship activities were carried out according to established guidelines, yet coordination among students, supervisors, and partner institutions was not always optimal. In the product aspect, quantitative data show significant improvements in students’ administrative, managerial, and practical work competencies. Overall, the study concludes that the MBKM internship program in the Islamic Education Management Study Program at UIN Palopo has been effectively implemented, although improvements are needed in partner selection and mentoring mechanisms. These findings provide recommendations for enhancing the quality of internship implementation in the future.